2000
DOI: 10.1111/j.1460-2466.2000.tb02862.x
|View full text |Cite
|
Sign up to set email alerts
|

Entertainment-Education and Social Change: An Analysis of Parasocial Interaction, Social Learning, Collective Efficacy, and Paradoxical Communication

Abstract: Most past studies of entertainment-education programs have not provided an adequate theoretical explanation of the process through which community members enact system-level changes as a result of exposure to entertainment-education media messages. Here we study the effects of an entertainment-education radio soap opera by means of an observational case study in one Indian village. We investigate the paradoxes, contradictions, and audience members' struggles in the process of media-stimulated change, a process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(72 citation statements)
references
References 50 publications
0
64
0
8
Order By: Relevance
“…EE has been defined as “the process of purposely designing and implementing a media message to both entertain and educate, in order to increase audience members’ knowledge about an educational issue” (Singhal & Rogers, 2004, p. 5). The designs of EE interventions differ widely, from bi-weekly television soap operas (Papa et al, 2000) to one-time video interventions lasting less than ten minutes (e.g., Chiasson et al, 2009; Love, Mouttapa, & Tanjasiri, 2009; Will, Sabo, & Porter, 2009). They also greatly differ in regards to their subject matter, from sexually transmitted infection awareness (Downs et al, 2004), to breast cancer awareness and screenings (Borrayo, 2004; Jibaya et al, 2000), to the use of booster seats for children (Will et al, 2009).…”
Section: Interventionmentioning
confidence: 99%
“…EE has been defined as “the process of purposely designing and implementing a media message to both entertain and educate, in order to increase audience members’ knowledge about an educational issue” (Singhal & Rogers, 2004, p. 5). The designs of EE interventions differ widely, from bi-weekly television soap operas (Papa et al, 2000) to one-time video interventions lasting less than ten minutes (e.g., Chiasson et al, 2009; Love, Mouttapa, & Tanjasiri, 2009; Will, Sabo, & Porter, 2009). They also greatly differ in regards to their subject matter, from sexually transmitted infection awareness (Downs et al, 2004), to breast cancer awareness and screenings (Borrayo, 2004; Jibaya et al, 2000), to the use of booster seats for children (Will et al, 2009).…”
Section: Interventionmentioning
confidence: 99%
“…Evidence supporting the involvement of parents in Relationship and Sexuality Education has become increasingly common since then 69 and, in recent times, studies 61,68,70 have demonstrated the importance of embracing such modalities as engaging adjuncts to school-based education.…”
Section: Evidence Supporting the Use Of Skills-building Componentsmentioning
confidence: 99%
“…This electronic communication approach was successfully piloted in the feasibility study. Recent studies 68,69,148 demonstrate the importance of embracing such 'education entertainment' modalities as engaging adjuncts to school-based education. This refinement has been funded by the Health and Social Care Research and Development Office of Northern Ireland (HSC R&D).…”
Section: Secondary Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…soap operas and episodic radio shows) in communities as diverse as Mexico, India, Tanzania, and China (Bandura, 2006). Such programs were designed to promote causes such as family planning (Rogers et al, 1999), HIV prevention (Vaughan, Rogers, Singhal, & Swlehe, 2000), egalitarian gender practices (Papa et al, 2000), women's access to education (Bandura, 2006), environmental sustainability (Bandura, 2002), and more. Many of the 75+ series were quite popular, airing at prime time and enjoying viewerships in the millions.…”
Section: Introductionmentioning
confidence: 99%